Tribological analysis of advanced microwave synthesized Molybdenum disulfide (MoS2) as anti-friction additives in diesel engine oil for military vehicles. (2022) - Thachnatharen, N.; Khalid, M.; Shahabuddin, S.; Anwar, A.; Sridewi, N.
Abstract: One of the most important method to reduce friction and wear is lubrication which is important in the automotive industry for energy efficiency, environmental conservation, and carbon reduction. Additionally, incorporating nanoparticles into engine oil lubricants can significantly increase their performance, particularly in terms of tribological properties. Advanced microwave synthesized Molybdenum disulfide (MoS2 ) anti-friction additive in SAE 20 W50 diesel engine oil was employed to formulate the nanolubricant. Fourier-transform infrared spectroscopy (FTIR) and a physical stability observation test was used to study the nano additives' physicochemical qualities (MoS2 ). The tribological performance of the MoS2 nanolubricant was measured using the four-ball tribotester. The Coefficient of Friction (COF) and average Wear Scar Diameter (WSD) of the anti-friction additives were analysed through tribological investigations of the wear rate and scar of the worn-out surface on ball bearings. MoS2 based nanolubricant improves COF and WSD by 10.25 % and 10.6 % respectively, as a contrast to the engine oil revealed from the tribological analysis. The current study discovered that the engine oil with advanced microwave synthesized nanoparticles have a significantly lower COF and WSD than engine oil which is not added with the anti-friction additives.